How do practitioners capture and utilize user feedback during continuous software engineering? - Johanßen, Jan Ole; Kleebaum, Anja; Paech, Barbara (2019 IEEE 27th International Requirements Engineering Conference, 2019)
Continuous software engineering (CSE) evolved as a process for rapid software evolution. Continuous delivery enables developers to frequently retrieve user feedback on the latest software increment. Developers use these insights for requirements validation and verification. Despite the importance of users, reports about user feedback in CSE practice are sparse. We conducted 20 interviews with practitioners from 17 companies that apply CSE. We asked practitioners how they capture and utilize user feedback. In this paper, we detail the practitioners' answers by posing three research questions. To improve continuous user feedback capture and utilization with respect to requirements engineering, we derived five recommendations: First, internal sources should be approached, as they provide a rich source of user feedback; second, existing tool support should be adapted and extended to automate user feedback processing; third, a concept of reference points should be established to relate user feedback to requirements; fourth, the utilization of user feedback for requirements validation should be increased; and last, the interaction with user feedback should be enabled and supported by increasing developer-user communication. We conclude that a continuous user understanding activity can improve requirements engineering by contributing to both the completeness and correctness of requirements.
Gesehen am 16.12.2019